2018
DOI: 10.1021/acs.est.8b00004
|View full text |Cite
|
Sign up to set email alerts
|

Lead Speciation and Association with Organic Matter in Various Particle-Size Fractions of Contaminated Soils

Abstract: Lead (Pb) stabilization in polluted soils treated by a Pb immobilization technique may be dependent on the speciation of Pb present in specific particle-size fractions of the soil. However, the scale-dependency of Pb speciation in contaminated soils is still not clearly understood. In this study, the natures and amounts of Pb chemical forms were determined in five Pb-polluted soil samples from Klity Village, Thailand, and their particle-size fractions. This was achieved using multiple analytical tools, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Estimates of RBA > 1 suggest that the soil contained a Pb species that was more bioavailable than Pb 2+ produced from dissociation of lead acetate, the soluble reference Pb compound. RBAs > 1 have been reported from swine studies of soils enriched with highly soluble lead carbonate . However, as noted below, there was no evidence of lead carbonate or other highly soluble forms of Pb in the diets that were amended with soil and fed to mice.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Estimates of RBA > 1 suggest that the soil contained a Pb species that was more bioavailable than Pb 2+ produced from dissociation of lead acetate, the soluble reference Pb compound. RBAs > 1 have been reported from swine studies of soils enriched with highly soluble lead carbonate . However, as noted below, there was no evidence of lead carbonate or other highly soluble forms of Pb in the diets that were amended with soil and fed to mice.…”
Section: Resultsmentioning
confidence: 70%
“…RBAs > 1 have been reported from swine studies of soils enriched with highly soluble lead carbonate. 41 However, as noted below, there was no evidence of lead carbonate or other highly soluble forms of Pb in the diets that were amended with soil and fed to mice.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The observation that extractable Pb did not appear to increase as a result of biosolids application despite an increase in total soil Pb can be attributed to the greater organic matter content and higher pH of the amended soils (Table 2). The strong affinity of organic matter in soils for Pb [37,38] is likely to have prevented measurable increases in Pb extractability. The Modified Morgan extractable P test results (Table 4) revealed extreme excesses of bioavailable P (as high as 687 mg kg −1 P) in the biosolids-amended soils.…”
Section: Extractable and Leachable Soil Elementsmentioning
confidence: 99%
“…Nonetheless, recent research showed that the effect of PSM on Pb mobility could be further complicated due to the diversity of factors in the soil environment. For example, the decrease of soil pH promoted the dissolution of Pb, and the change of the soil microstructure affected the precipitation and adsorption process of Pb . Additionally, the introduction of new species can change the direction of the succession of soil microbial communities, and the changes in the soil microbial community structure and function may be important factors in the MIPP process. , Studies found that exogenous inoculation of PSM can increase the abundance of Pb-tolerant dominant genera and P-solubilization genes in soil, thus strengthening the P-cycling potential of indigenous microorganisms .…”
Section: Introductionmentioning
confidence: 99%